First isolation of a methicillin-resistant Staphylococcus aureus from bovine mastitis in Argentina - Srednik, Mariela Elizabeth (2018)
This research communication describes the first isolation of a methicillin-resistant Staphylococcus aureus (MRSA) from cow´s mastitic milk in Argentina. Bovine mastitis causes important economic losses in the dairy industry and the most commonly isolated bacteria from bovine mastitis are staphylococci. The mecA gene present in MRSA bacteria confers resistance to almost all β-lactam antibiotics, the most frequent drugs used in bovine mastitis therapy.